3D QSAR and Pharmacophore Modelling on Chalcones as Antileishmanial Agents potential Trypanothione reductase Inhibitors - Sujit Arun Desai, Santosh Sahedeo Kumbhar, Vishal Shankar Katti, Prafulla Balkrishna Choudhari, Manish Sudesh Bhatia (Journal of Applied Pharmaceutical Science, 2013)
Chalcones is an important auxiliary having various important clinical applications. A series of Chalcones as antileishmanial agents by were reported. Three dimensional quantitative structure-activity relationship (3D-QSAR), including, were performed to elucidate the 3D structural features which are important for the antileishmanial activity. The results of 3D QSAR model (q2 = 0.8100, r2 = 0.9355,) exhibited the highly degree of statistical significance and good predictive ability. The results generated 3D QSAR can provide important information about the structural characteristics which are contributors of the inhibitory potency of chalcones. In addition, docking analysis and pharmacophore mapping was applied to identify the binding modes between the ligands and the Trypanothione reductase and structural features of the ligands which are important for the biological activity of the molecules. The information obtained from this study could provide vital information for future development of potent instructions for the further development of potent antileishmanial agents as trypanothione reductase inhibitors.
Keywords: Chalcone, 3DQSAR, Pharmacophore, Docking, Trypanothione reductase.